An Analysis in Using Learning Media to Increase Student Motivation of Learning Physics - Reni Dwi Puspitasari; Ummu Mulkiyah (CV. Tripe Konsultan, 2023)
This study aims to determine the effect of using instructional mediaonline on the motivation of learning physics class XI MIPA SMAN 1 Sendang Agung. The type of research used is qualitative research with data collection instruments using questionnaires and interviews with teachers and students. The class sample taken was class IX MIPA two classes with a total of 30 students each. The results showed that the average level of learning motivation was included in the high criteria after using learning mediaonline that is, with a percentage of 80% compared to the use of printed learning media such as books and LKS modules, namely 40% in the low category. Research on the learning motivation of class XI MIPA students of SMAN 1 Sendang Agung shows that the average level of learning motivation is included in the high criteria. Many factors influence the contribution to the achievement of the average student score, one of which is learning motivation. Motivation to learn is very important in the learning process because the learning process requires active interaction and participation from students to succeed.